Effective use of management resources in the implementation of the project «Sport is the norm of life» - Frunze V.V. ,; Kolesnikov N.V. ,; Ponimasov O.E. , (Theory and Practice of Physical Culture, 2024)
Objective of the study is to reveal the potential of a rationally oriented management strategy for the federal project «Sport is the norm of life», increasing the efficiency of its practical implementation in the federal city of St. Petersburg. Methods and structure of the study. The object-subject segment of the study is the analysis of cause-and-effect relationships of the implementation of the project «Sport is the norm of life» based on achieving resource-functional compatibility of management algorithms. Results and conclusions. The rational use of management algorithms in the implementation of the project «Sport is the norm of life» ensures the solution of multifunctional problems of preserving human capital and the health of the population of St. Petersburg.